2015
DOI: 10.1371/journal.pone.0145324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glycosylation Inhibition on the Binding of KIR3DL1 to HLA-B*57:01

Abstract: Viral infections can affect the glycosylation pattern of glycoproteins involved in antiviral immunity. Given the importance of protein glycosylation for immune function, we investigated the effect that modulation of the highly conserved HLA class I N-glycan has on KIR:HLA interactions and NK cell function. We focused on HLA-B*57:01 and its interaction with KIR3DL1, which has been shown to play a critical role in determining the progression of a number of human diseases, including human immunodeficiency virus-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…These proteins have in common the complex post-translational modification that requires N-glycosylation for the correct localization (HFE), activation (TMPRSS6), and stabilization (TFR2) in the plasma membrane [44][45][46]. As proof of concept, we treated HuH7 cells with tunicamycin, an N-linked glycosylation inhibitor [47]. Treatment with increasing concentrations of tunicamycin demonstrated that the altered glycosylation led to a reduced expression of TFR2, HFE, and TMPRSS6 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins have in common the complex post-translational modification that requires N-glycosylation for the correct localization (HFE), activation (TMPRSS6), and stabilization (TFR2) in the plasma membrane [44][45][46]. As proof of concept, we treated HuH7 cells with tunicamycin, an N-linked glycosylation inhibitor [47]. Treatment with increasing concentrations of tunicamycin demonstrated that the altered glycosylation led to a reduced expression of TFR2, HFE, and TMPRSS6 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-B*57:01 of the DBB and DEM cells displays a Bw4 motif, while B*07:02 of JY cells displays a Bw6 motif. HLA molecules harboring the Bw4 motif have been shown to elicit a stronger NK-cell response and the glycan attached to the HLA heavy chain is required for the NK-cell interaction . There may thus be a link between this Bw motif, the HLA glycosylation pattern, and the interaction with NK-cell KIR cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured for 1 week in custom-made Advanced RPMI-1640 (Life Technologies) with magnesium sulfate, zinc sulfate, and copper (II) sulfate replaced with their respective chloride salts, and supplemented with fetal calf serum (Sigma), GlutaMAX (Gibco), penicillin/streptomycin, and 150 mM sodium chlorate (Sigma) as described previously 75 . Cells were then used in the viral fusion assay as described.…”
Section: Methodsmentioning
confidence: 99%